The impact of collaborative CPD on classroom teaching and learning : How does collaborative Continuing Professional Development (CPD) for teachers of the 5-16 age range affect teaching and learning? - Rundell, Barbara; Seddon, Katy (EPPI-Centre, Social Science Research Unit, Institute of Education, University of London., 2003)
London: EPPI-Centre, Social Science Research Unit, Institute of Education, University of London.